The craft of political research - Shively, W. Phillips, 1942- (Pearson classics in political science, 2013)
The Craft of Political Research immerses readers not only in how political scientists work but also in how ideas produce research questions and guide the selection of research methods. Emphasizing the internal logic of research methods and the collaborative nature of the research process, this slender text explores the design behind interesting questions, problems in measurement and analysis, and key statistical methods. The Craft of Political Research's elegant explanations inspire a big picture understanding of how political scientists explain political reality and encourage students to create their own inventive, original, and bold research work.